The Influence of Socio-Cultural Factors on the Activities of a Modern Organization ("Journal "U". Economy. Management. Finance.", 2022)
Currently, there is a significant increase in the influence of socio-cultural factors on business and management activities in various companies in the territory of the Russian Federation. This is primarily due to the fact that there are a large number of international companies in Russia that introduce certain elements into the work of not only their employees, but also employees of organizations that express a desire to apply similar approaches and technologies in their companies. Even now, when many international companies have suspended their activities in the Russian Federation or left the Russian market altogether, a large number of foreign representatives remain in the country, which means that the market continues to change.
Keywords: cultural intelligence; management; modern organization; socio-cultural factors; stereotyping; labor relations; personnel management